2011
DOI: 10.4088/pcc.08m00748blu
|View full text |Cite
|
Sign up to set email alerts
|

Correction for "'Caseness' for Depression and Anxiety in a Depressed Outpatient Population

Abstract: Objective: To examine the diagnostic status of patients enrolled in the Factors Influencing Depression Endpoints Research (FINDER) study and symptomatic outcomes and baseline characteristics associated with remission 6 months after commencing antidepressant therapy.Method: Status of clinically diagnosed depressed patients was based on self-rated Hospital Anxiety and Depression Scale (HADS) scores. Five diagnostic categories were defined: noncaseness, mixed anxiety-depression (subthreshold depressive and anxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Previous studies have found that moderate to severe pain is common in patients with depression 31,37. More severe pain has been associated with more severe depression,38 a worse course of depression,10,39 a lower likelihood of or longer time to response or remission,15,40,41 a poorer health-related quality of life,14 and increased health care utilization 10. Recent data extracted from the GPRD has shown greater health service use and costs in patients with non-remission of depression compared with those who achieve remission (defined as successful cessation of antidepressant treatment for at least 6 months) 42…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that moderate to severe pain is common in patients with depression 31,37. More severe pain has been associated with more severe depression,38 a worse course of depression,10,39 a lower likelihood of or longer time to response or remission,15,40,41 a poorer health-related quality of life,14 and increased health care utilization 10. Recent data extracted from the GPRD has shown greater health service use and costs in patients with non-remission of depression compared with those who achieve remission (defined as successful cessation of antidepressant treatment for at least 6 months) 42…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently suggested the existence of a bidirectional relationship between oxidative stress inflammation and these conditions (Demyttenaere et al, 2009;Liu et al, 2018;Prenderville, Kennedy, Dinan, & Cryan, 2015;Straub & Cutolo, 2018). Previous investigations have suggested that oxi-inflammatory states triggered by depression and/or chronic psychological stress appear to be associated with the elevation of reactive oxygen species (ROS) (Lopresti, Maker, Hood, & Drummond, 2014), including superoxide anion levels produced by NADPH oxidase activation or some impairment in superoxide dismutase (SOD) enzymes (Seo et al, 2012;Uchihara, Tanaka, Asano, Tamura, & Mizushima, 2016;Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with depression are often comorbid with anxiety, which is related to a greater severity and a poorer treatment prognosis [ 17 , 18 ]. Anxiety disorders also interact with PPS [ 19 - 21 ]; for example, a patient with generalized anxiety disorder (GAD) has a greater severity of PPS as compared with a control [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As described above, MDD, migraine, anxiety disorders, and PPS are closely related and interact [ 1 , 2 , 14 , 21 , 22 ]. Although many studies have investigated the impacts of migraine and anxiety disorders on patients with MDD [ 12 , 16 - 18 , 23 ], no study has reported the impacts of migraine and anxiety disorders on PPS among patients with MDD, to the best of our knowledge. Investigating the above issue is mandatory.…”
Section: Introductionmentioning
confidence: 99%